2006
DOI: 10.1063/1.2424670
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative observation and discrimination of AlGaN- and GaN-related deep levels in AlGaN∕GaN heterostructures using capacitance deep level optical spectroscopy

Abstract: Deep levels were observed using capacitance deep level optical spectroscopy ͑DLOS͒ in an AlGaN / GaN heterostructure equivalent to that of a heterojunction field effect transistor. Band gap states were assigned to either the AlGaN or GaN regions by comparing the DLOS spectra in accumulation and pinch-off modes, where the former reflects both AlGaN-and GaN-related defects, and the latter emphasizes defects residing in the GaN. A band gap state at E c − 3.85 eV was unambiguously identified with the AlGaN region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…The E C -3.25 has been previously reported to be a GaN buffer trap that correlates with the presence of residual carbon manifesting as C N substitutional defects [14][15][16]. The E C -3.8 eV, simply by virtue of its activation energy being larger than the GaN bandgap, must be an AlGaN trap, and has been reported previously [17]. On-resistance data collected from DC output IV of the GaN HEMT before and after stress in the dark, with 1.2 eV, and with 3 eV monochromatic light shining on the GaN HEMT.…”
Section: Resultsmentioning
confidence: 86%
“…The E C -3.25 has been previously reported to be a GaN buffer trap that correlates with the presence of residual carbon manifesting as C N substitutional defects [14][15][16]. The E C -3.8 eV, simply by virtue of its activation energy being larger than the GaN bandgap, must be an AlGaN trap, and has been reported previously [17]. On-resistance data collected from DC output IV of the GaN HEMT before and after stress in the dark, with 1.2 eV, and with 3 eV monochromatic light shining on the GaN HEMT.…”
Section: Resultsmentioning
confidence: 86%
“…Early studies revealed that gate lag and drain current collapse in HFET devices were related to traps in the AlGaN surface and GaN buffer layers. 1 Many techniques, such as photoionization spectroscopy, 2 deep level transient spectroscopy ͑DLTS͒, 3 deep level optical spectroscopy ͑DLOS͒, 4,5 and current-DLTS on HFETs, 6 have been used to study traps in AlGaN/GaN structures. Carbon is a common residual impurity in unintentionally doped ͑UID͒ GaN buffer layers grown by metalorganic chemical vapor deposition ͑MOCVD͒ but the carbon concentration and resistivity in these layers can be controlled by growth pressure.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although photoluminescence ͑PL͒ or cathodoluminescence ͑CL͒ investigation has shown some characteristic luminescence peaks related to deep electronic levels in AlGaN and AlN, 3-7 electrical characterization on deep levels in AlGaN or AlGaN/GaN heterostructure has been reported only a few times. [8][9][10][11] In particular, the deep-level transient spectroscopy ͑DLTS͒ method only detected deep levels with activation energies under 0.9 eV, 10 in spite of the fact that a near-midgap level can act as a dominant recombination center rather than a level near conduction or valence band. To detect near-midgap levels in AlGaN, a temperature range should extend to 800 K in a typical DLTS measurement condition.…”
mentioning
confidence: 99%